DC-Derived IL-10 Modulates Pro-inflammatory Cytokine Production and Promotes Induction of CD4+IL-10+ Regulatory T Cells during Plasmodium yoelii Infection - Loevenich, Katharina; Ueffing, Kristina; Abel, Simone; Hose, Matthias; Matuschewski, Kai; Westendorf, Astrid M.; Buer, Jan; Hansen, Wiebke (Frontiers in Immunology, 2017)
The cytokine IL-10 plays a crucial role during malaria infection by counteracting the pro-inflammatory immune response. We and others demonstrated that Plasmodium yoelii (P. yoelii) infection results in enhanced IL-10 production in CD4+ T cells accompanied by the induction of an immunosuppressive phenotype. However, it is unclear whether this is a direct effect caused by the parasite or an indirect consequence due to T cell activation by IL-10 producing antigen-presenting cells. Here, we demonstrate that CD11c+CD11b+CD8- dendritic cells (DCs) produce elevated levels of IL-10 after P. yoelii infection of BALB/c mice. DC-specific ablation of IL-10 in P. yoelii-infected IL-10flox/flox/CD11c-cre mice resulted in increased IFN-g and TNF-a production with no effect on MHC-II, CD80 or CD86 expression in CD11c+ DCs. Accordingly, DC-specific ablation of IL-10 exacerbated systemic IFN-g and IL-12 production without altering P.yoelii blood stage progression. Strikingly, DC-specific inactivation of IL-10 in P. yoelii-infected mice interfered with the induction of IL-10 producing CD4+ T cells while raising the frequency of IFN-g secreting CD4+ T cells. These results suggest that P. yoelii infection promotes IL-10 production in DCs, which in turn dampens secretion of pro-inflammatory cytokines and supports the induction of CD4+IL-10+ T cells.